Nanosecond-time-scale delayed fluorescence molecule for deep-blue OLEDs with small efficiency rolloff - Jong Uk Kim (Nature Portfolio, 2020)
Deep-blue emitting organic materials with low exciton lifetime are required to realize efficient organic light-emitting diodes (OLEDs) at high brightness. Here, the authors report deep-blue OLEDs featuring thermally activated delayed fluorescence molecules with subnano-second exciton lifetime.